The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/ta.0b013e31823ba29e
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Tracheostomy: To Bronch or Not to Bronch—That Is the Question

Abstract: Percutaneous tracheostomy was safely and effectively performed by an experienced surgical team both with and without bronchoscopic guidance with no difference in the complication rates. This study suggests that the use of bronchoscopic guidance during tracheostomy is not routinely required but may be used as an important adjunct in selected patients, such as those with HALO cervical fixation, obesity, or difficult anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 20 publications
1
56
1
6
Order By: Relevance
“…This probably results from the addition of FOB for percutaneous tracheostomy and the definition of its utility. Some authors would argue that FOB is not mandatory for percutaneous tracheostomy [32,33]. We would disagree.…”
Section: Discussionmentioning
confidence: 98%
“…This probably results from the addition of FOB for percutaneous tracheostomy and the definition of its utility. Some authors would argue that FOB is not mandatory for percutaneous tracheostomy [32,33]. We would disagree.…”
Section: Discussionmentioning
confidence: 98%
“…The largest comparative study did not show a difference in complication rates with the use of video bronchoscopy. 22 In fact, the most significant complication (loss of airway and subsequent cardiac arrest) occurred in the bronchoscopy group. Although there is a lack of evidence in the literature, blind PDT without direct visualization of the trachea might be associated with an increased risk of uncentered tracheal positioning, paratracheal insertion, and posterior tracheal wall laceration or perforation with subsequent potential for increased incidence of complications based on our experience.…”
Section: Discussionmentioning
confidence: 99%
“…5 Pre-procedural ultrasound examination of the neck decreases bleeding complications, whereas a DLET does not address this issue. Thus, even with a DLET, a pre-procedural ultrasound exam should be performed.…”
Section: To the Editormentioning
confidence: 99%
“…A retrospective review found no difference in PDT complications with or without bronchoscopy. 5 Only 50% of operators worldwide use bronchoscopy. 2,3 Large studies using either intermittent bronchoscopy or no bronchoscopy at all during PDT have shown very low complication rates, very low mortality, and high success rates even in high-risk subjects.…”
Section: To the Editormentioning
confidence: 99%